Wikis and Collaborative Learning / Yun-Ke Chang, Miguel Angel Morales-Arroyo, Hla Than... [et.al]. - Chang, Yun-Ke; Morales-Arroyo, Miguel Angel; Than, Hla; Tun, Zarchi; Wang, Zhujun (2011)
Wikis have been used as a supporting tool for students‘ learning and collaboration. Tasks such as collaborative writing, joined glossaries creation, document discussion and review, group projects, reflection journals and others have been tried out using wikis as a facilitating tool (Ben-Zvi, 2007). However, few studies have reported how students actually perceive some well-claimed benefits. This study investigated the perception of learning activities facilitated by wiki, and the effectiveness of several roles wiki might play in constructive and collaborative learning. This study tried to answer the following questions. How do students perceive a wiki as a learning tool? How does a wiki support constructive learning skills? How does a wiki support student‘s collaborative learning skills? How does collaboration in wiki facilitate students‘ content learning and project work? The study was conducted using a survey method to examine the perception of wiki usage and collaborative and constructive learning. In the reported study, a questionnaire was used to collect data from 92 students in higher education. The results suggest that using wikis were perceived to enhance collaborative knowledge building among students, but it did not contribute much to learning the subject matters although students were more involved in the learning process than with conventional teaching methods. In another word, it indicates that students may not obtain better return of investment on the time spent in using wiki as a learning tool. While wiki did contribute to enrich the learning experience, further study is needed to investigate how to link learning process with learning outcome using this type of collaboration tools.